2021
DOI: 10.2174/0929867327666200330143338
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles as a Tool for Broadening Antifungal Activities

Abstract: : The Fungal infections are diseases that are considered neglected although their infection rates have increased worldwide in the last decades. Thus, since the antifungal arsenal is restricted and many strains have shown resistance new therapeutic alternatives are necessary. Nanoparticles are considered important alternatives to promote drug delivery. In this sense, the objective of the present study was to evaluate the contributions of newly developed nanoparticles to the treatment of fungal infections. Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 284 publications
(290 reference statements)
0
8
0
Order By: Relevance
“…The observed results on lamentous fungi con rmed that the silver nanoparticles enhanced the antifungal behavior against mycelium and spores [39]. Numerous works, described the antifungal potential of Olive plant against lamentous fungi like Rhizopus, Fusarium and Alternaria as reported by [40]. These funding mentioned that the antifungal behavior of the biosynthesized silver nanoparticles from mixed extracts could be due to the olive composition, which was able to affect the spores and the mycelium fungi growth.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The observed results on lamentous fungi con rmed that the silver nanoparticles enhanced the antifungal behavior against mycelium and spores [39]. Numerous works, described the antifungal potential of Olive plant against lamentous fungi like Rhizopus, Fusarium and Alternaria as reported by [40]. These funding mentioned that the antifungal behavior of the biosynthesized silver nanoparticles from mixed extracts could be due to the olive composition, which was able to affect the spores and the mycelium fungi growth.…”
Section: Discussionmentioning
confidence: 83%
“…Numerous studies have shown that nanoparticles generally improved the pharmaceutical characteristics of antifungals, as lower toxicity and enhancing antifungal potential, and the possibility of prolonged action [40]. The reported data show that the presence of AgNPs in the Candida growth can limit the virulence factor as enzyme production and bio lm formation.…”
Section: Discussionmentioning
confidence: 98%
“…Another promising possibility is to use nanoparticles for drug delivery, as they improve the biopharmaceutical and pharmacokinetic properties of antifungal agents. These characteristics are further reflected in a greater pharmacodynamic potential, lower toxicity, and prolonged action [147]. In particular, polymeric nanoparticles are attractive due to their two-fold role: drug nanocarrier and intrinsic antimicrobial agent [52].…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…Transdermal delivery of nanoparticles has gained a great interest in topical antifungal therapy provided by high drugs penetration rate and controllability of gradual or triggered encapsulated payload release. Active development of various nano- and micron-sized systems for transdermal drug delivery opens up the possibilities for antifungal therapy improvement [53]. Serving as a local (isolated) drug depot and providing a mechanism for controlled release, such systems can deliver high topical concentrations of drugs without pronounced systemic spread [54].…”
Section: Nanocarriers For Intradermal Permeation and Antimycotic Actimentioning
confidence: 99%